The impact of hypoglycaemia in children and adolescents with type 1 diabetes on parental quality of life and related outcomes: A systematic review. Issue 3 (23rd January 2022) - Jensen, Mette Valdersdorf; Broadley, Melanie; Speight, Jane; Chatwin, Hannah; Scope, Alison; Cantrell, Anna; Heller, Simon; de Galan, Bastiaan E.; Hendrieckx, Christel; Pouwer, Frans; ,
Abstract: This systematic review aims to summarize and critically evaluate the current evidence regarding the impact of hypoglycaemia in children and adolescents with type 1 diabetes on parental quality of life. MEDLINE, PsycINFO, CINAHL, and the Cochrane Library were searched. Inclusion criteria were: 1) quantitative design, 2) included parents of children or adolescents with type 1 diabetes, 3) assessment of hypoglycemia in children/adolescents with type 1 diabetes, 4) assessment of parent quality of life (or related domains of life), and 5) analysis of the relationship(s) between the child's hypoglycaemia and parents' quality of life. The data were summarised in accordance with Synthesis Without Meta‐Analysis Guidelines. Twelve studies were included, reporting data from 1895 parents across six countries. Ten studies were cross‐sectional; two included prospective data. Evidence suggested that greater frequency and severity of hypoglycemia was associated with greater parental fear of hypoglycemia, emotional distress and family burden. Children's hypoglycaemia has a negative impact on the well‐being of parents, but there is an absence of evidence regarding the impact on their overall quality of life. Research into the hypoglycaemia‐specific quality of life of parents is needed to explore the impact on various areas, such as social and physical dimensions.